Karakteristik Pembakaran Briket Tandan Kosong Kelapa Sawit dan Emisi Gas Karbon Monoksida (CO) dari Pembakaran dengan Kompor Biomassa Variasi Bukaan Lubang Udara - Hafidawati, Hafidawati; Yenie, Elvi; Agustariza, Alen (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2024)
Waste oil empty palm fruit bunches (EFB) one of the renewable energy sources with great potential and is produced approximately 21% of the entire palm oil processing process. Burning EFB briquettes using biomass stoves has a low combustion efficiency, so it has the potential to emit CO. The aim of this research is to determine CO gas emissions resulting from burning empty palm fruit bunch briquettes with variations in the number of holes in the biomass stove and compare them with the quality standards of Minister of Energy and Mineral Resources Regulation No. 047 of 2006. and see how the effect of air hole openings on biomass stoves with empty palm fruit bunch briquettes. In this study, co emission test was conducted using environmental combustion analyzer type 450 and biomass stove performance using water boiling test method. Testing was conducted with variations of air hole openings L1 (3.51 cm2), L2 (7.03 cm2), and L3 (10.55 cm2). The results of CO gas testing obtained by L1, L2 and L3 are 523.54 mg/ Nm3, 425.59 mg/ Nm3, and 351.13 mg / Nm3 and still meet the quality standards of ESDM no. 047 of 2006. Thermal efficiency of briquette stoves obtained in L1, L2 and L3 are 26.51%, 24.28% and 22.28% and for specific consumption rates obtained in L1, L2 and L3 are 3.47 grams/minute, 5.54 grams/minute and 7.17 grams/minute, this result didn’t meet the quality standard of SNI 7926-2013. Based on the results of the study, it was concluded that the smaller the opening of the briquette stove air hole, the more CO emissions produced, the higher the thermal efficiency and the smaller the consumption rate.